THE METHODOLOGY OF EDUCATING HIGH SCHOOL STUDENTS IN THE SPIRIT OF LOYALTY TO MORAL VALUES - Eshqoʻziyeva Muhayyo Ermat qizi (TADQIQOTLAR, 2026)
Abstract: The education of high school students is a critical period that greatly impacts the formation of their personalities, worldviews, and attitudes towards life itself. Particularly in a rapidly changing global society, the role of instilling loyalty to moral values becomes increasingly essential for guiding adolescents through the challenges and choices they are faced with. The methodology for cultivating such loyalty requires a well-structured, holistic, and consistent approach that addresses the intellectual, emotional, and behavioral domains of the student’s development.